Barium titanate particle powder and production method and dispersion of the same
By controlling the average primary particle diameter and particle size distribution of Bali titanate particles and combining with the preparation method of solution reaction method, the interlayer peeling problem existing in the application of Bali titanate particle powder in high-performance small electronic and optical components in the prior art is solved, and the effects of high purity, low fusion and good particle size distribution are achieved.
Patent Information
- Application Number
- JP2023172079
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-03
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, when preparing high-performance small electronic and optical components, it is difficult to ensure the high purity, low fusion and good particle size distribution of Batitanate particle powder, resulting in interlayer peeling problems in applications such as MLCC.
By controlling the average primary particle diameter of the Batitanate particles between 20 nm and 80 nm, the particle diameter with a 50% cumulative frequency distribution is between 0.081 μm and 0.244 μm, and the probability of fusion between the primary particles is between 1% and 15%, and the solution reaction method is used to control the Ba/Ti composition ratio and the high purity of the particles.
The high purity, low fusion and good particle size distribution of Batitanate particle powder is achieved, improving its performance and reliability in small electronic and optical components, and reducing the risk of interlayer peeling in applications such as MLCC.
Smart Images

Figure 2025062804000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a barium titanate particle powder, a manufacturing method thereof, and a dispersion thereof. More specifically, the present invention relates to a barium titanate particle powder which is fine, has little fusion between primary particles, has an excellent particle size distribution of aggregate particle diameters, has a low ignition loss, and is highly crystalline, and therefore is easily dispersed in a solvent, and is therefore suitable as a raw material for small, high-performance electronic and optical components, and can also be suitably used in multilayer ceramic capacitors (MLCCs), and to a manufacturing method thereof and a dispersion thereof. [Background technology]
[0002] In recent years, there has been an accelerating trend towards making electronic devices such as mobile phones and personal computers smaller and lighter, which has resulted in the capacitors in the electrical circuits contained in these devices becoming smaller and larger in capacity, as well as the optical films becoming smaller and more highly transmittant.
[0003] 2. Description of the Related Art With the trend toward smaller electronic and optical components, higher capacity, and higher transmittance, there is an increasing demand for barium titanate particles that are highly crystalline and fine, and that can be easily dispersed in various solvents.
[0004] From the viewpoint of making the barium titanate particle powder-containing resin film used for the above-mentioned parts thinner, there is an increasing demand for barium titanate particle powder that can be easily dispersed in various solvents.
[0005] In addition, in a multilayer ceramic capacitor (hereinafter referred to as "MLCC") in which dielectric layers and internal electrode layers are alternately stacked, barium titanate particle powder is used as the raw material for the dielectric layers, and Ni particle powder is used as the raw material for the internal electrode layers.
[0006] In recent years, MLCCs have become smaller and have larger capacities, and the thicknesses of the dielectric layers and internal electrode layers are each 1 μm or less. This means that the particle sizes of the raw materials, barium titanate particle powder and Ni particle powder, are also required to be submicron or smaller.
[0007] MLCCs are typically manufactured by preparing a slurry or paste for forming the dielectric layers and the internal electrode layers, and then alternately stacking and firing dry films of the slurry, etc., so that the Ni particles in the internal electrode layers and the barium titanate particles in the dielectric layers are sintered at the same time.
[0008] However, Ni particles of submicron size or smaller are sintered at temperatures several hundred degrees lower than barium titanate particles of the same size, and the difference in thermal contraction properties between Ni particles and barium titanate particles creates the problem that peeling easily occurs between the laminated dielectric layers and internal electrode layers.
[0009] A highly crystalline, fine barium titanate particle powder that can be easily dispersed in a solvent can be suitably used as a raw material for small electronic and optical components.
[0010] Furthermore, in the case of barium titanate particle powder, which has the above-mentioned properties as well as low ignition loss, when used in MLCCs and sintered, peeling between the dielectric layer and Ni internal electrode layer is unlikely to occur, and it is expected that MLCCs with high mechanical reliability can be manufactured. [Prior art documents] [Non-patent literature]
[0011] [Non-Patent Document 1] Edited by Takeshi Nomura, "Latest Trends in Materials, Manufacturing, and Mounting Technologies for Multilayer Ceramic Capacitors (MLCC)," published by R&D Support Center, Inc., October 30, 2020 [Non-Patent Document 2] Science and Technology Agency, Inorganic Materials Research Institute, Research Report No. 19, "Study on Titanium Oxide," 1979 [Patent documents]
[0012] [Patent Document 1] JP 2005-289668 A Summary of the Invention [Problem to be solved by the invention]
[0013] Non-Patent Document 1 and Patent Document 1 disclose the use of fine, highly dispersible barium titanate particles as a sintering retarder for Ni particles.
[0014] However, the techniques described in Non-Patent Document 1 and Patent Document 1 require the use of a large amount of dispersant as a co-material to disperse the barium titanate particles among the Ni particles, or require the application of a strong mechanical shear to disperse the particles.
[0015] However, if a large amount of dispersant is used or strong shear is applied, chipping of barium titanate particles and Ni particles occurs, and therefore it may not be possible to use it as a raw material for thin-layer ceramic capacitors or small electronic and optical components.
[0016] The inventors of the present invention have set a technical objective of solving the above problems, and as a result of numerous trial and error trials and experiments, have discovered that the average primary particle diameter is 20 nm or more and 80 nm or less, and the 50% diameter D of the cumulative frequency distribution of aggregated particles in an aqueous solvent is 1.0 mm or more. 50 and 95% diameter D 95 Represented by D 95 / D 50 The above-mentioned technical object has been achieved by obtaining the remarkable discovery that a barium titanate particle powder having a value of 1.2 or more and 5.0 or less, a probability of the presence of fused primary particles of 1% or more and 15% or less, and an ignition loss of 3.0% by weight or less is a highly crystalline and fine barium titanate particle powder that is easily dispersed in a solvent and has a low ignition loss. [Means for solving the problem]
[0017] The above technical object can be achieved by the present invention as follows.
[0018] That is, the present invention relates to a method for producing a granular aggregate having an average primary particle diameter of 20 nm or more and 80 nm or less, and a 50% diameter D of a cumulative frequency distribution of aggregated particles in an aqueous solvent. 50 and 95% diameter D95 Represented by D 95 / D 50 The barium titanate particle powder has a value of 1.2 or more and 5.0 or less, a probability of existence of fused primary particles is 1% or more and 15% or less, and an ignition loss is 3.0% by weight or less.
[0019] The present invention also relates to the barium titanate particles, wherein the coefficient of variation of the primary particle size is 0.30 or less.
[0020] The present invention also relates to the barium titanate particles, wherein a Ba / Ti composition ratio is 0.970 or more and 1.030 or less, and the barium carbonate content is 0.3 wt % or less.
[0021] The present invention also relates to the barium titanate particles, wherein the ignition loss is not more than (4.3-0.04×average primary particle diameter)% by weight.
[0022] The present invention also relates to a dispersion containing the barium titanate particles.
[0023] The present invention also provides a method for producing barium titanate particle powder by a solution reaction, the method comprising at least a first step of producing barium titanate using a titanium raw material that is a slurry containing titanic acid represented by TiO2·nH2O, where n is 0.5 or more and 1.5 or less, and the crystallite size of the anatase component is 2 nm or more and 10 nm or less; a second step of adjusting the titanium concentration of the reaction solution to 0.85 mol / L or more and 2.50 mol / L or less; and a third step of growing grains of barium titanate at 60°C or more and 155°C or less.
[0024] The present invention also relates to a method for producing barium titanate particle powder, wherein, in the solution reaction conditions of the first step, the raw material mixing temperature is 65°C or higher and 105°C or lower, the Ba / Ti is 0.80 molar ratio or higher and 1.25 molar ratio or lower, and the initial OH concentration is 0.8 mol / L or higher and 2.0 mol / L or lower.
[0025] The present invention also provides the method for producing barium titanate particles, wherein the barium titanate crystallite size in the solid content produced in the first step is 15 nm or more and 70 nm or less.
[0026] The present invention also provides the method for producing barium titanate particles, wherein in the second step, the Ba / Ti ratio in the reaction solution is set to 1.02 molar ratio or more and 1.50 molar ratio or less. Effect of the Invention
[0027] The barium titanate particle powder according to the present invention has a fine average primary particle diameter of 20 nm to 80 nm, little fusion between primary particles, an excellent particle size distribution of agglomerated particle diameters, and low ignition loss, and is therefore easily dispersible in various solvents and can be suitably used as a raw material for small, high-performance electronic and optical components. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 is a flow chart of a manufacturing method of the present invention. [Diagram 2] FIG. 2 is a transmission electron microscope (TEM) image (300,000 magnification) of the barium titanate particles of Example 2, with inter-particle fusion of primary particles additionally noted. [Diagram 3] FIG. 2 is a TEM image (300,000 times magnification) of the barium titanate particles of Comparative Example 1, with inter-particle fusion of primary particles additionally noted. [Figure 4] FIG. 2 is a TEM image (magnification: 500,000) of the barium titanate particles of Comparative Example 2, showing inter-particle fusion of primary particles. [Diagram 5] FIG. 2 is a diagram in which the ignition losses of Examples 1 to 4 and Comparative Examples 1 to 5, 13, and 14 are plotted against the average primary particle size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The configuration of the present invention will be described in more detail below.
[0030] First, the barium titanate particles according to the present invention will be described.
[0031] The average primary particle diameter of the barium titanate particles according to the present invention is from 20 nm to 80 nm, preferably from 22 nm to 70 nm, and more preferably from 24 nm to 60 nm.
[0032] If the average primary particle diameter is less than 20 nm, it is difficult to industrially, i.e., safely and mass-produce a barium titanate particle powder that satisfies the requirements of the present invention for the cumulative frequency distribution of agglomerated particles and the existence probability of fused primary particles, and if it exceeds 80 nm, there is a risk that it cannot be used for applications such as small electronic components and optical components.
[0033] The barium titanate particle powder according to the present invention has a diameter of 50% of the cumulative frequency distribution of aggregated particles in an aqueous solvent. 50 and 95% diameter D 95 Represented by D 95 / D 50 The value of is 1.2 to 5.0, preferably 1.3 to 4.5, and more preferably 1.4 to 4.3.
[0034] D 95 / D 50 When the value is 1.2 to 5.0, it can be considered that the particle is easily dispersed in an aqueous solvent.
[0035] D 95 / D 50 If the value is less than 1.2, it is difficult to industrially produce a particle powder that satisfies the requirement for the existence probability of fused primary particles in the present invention, and if it exceeds 5.0, it is difficult to say that the particle size distribution of the agglomerated particles is excellent, and there is a risk that the particles will not be easily dispersed in various solvents.
[0036] The aqueous solvent in the present invention is not particularly limited, but examples thereof include water, alcohol-based solvents, and glycol ether-based solvents.
[0037] A dispersant such as sodium hexametaphosphate may be added to the aqueous solvent in the present invention.
[0038] The probability of existence of fused primary particles in the barium titanate particles according to the present invention is 1% to 15%, preferably 2% to 14%, and more preferably 3% to 13%.
[0039] If the probability of existence of fused primary particles in the barium titanate particle powder of the present invention is less than 1%, it is difficult to industrially, i.e., safely and mass-produce barium titanate particle powder that satisfies the requirements of the cumulative frequency distribution of agglomerated particles and the probability of existence of fused primary particles in the present invention, and if it exceeds 15%, there is a risk that the barium titanate particle powder will not be easily dispersed in various solvents.
[0040] The ignition loss of the barium titanate particles according to the present invention is 3.0% by weight or less, preferably 2.9% by weight or less, and more preferably 2.8% by weight or less. The lower limit of the ignition loss is about 0.1% by weight.
[0041] If the ignition loss exceeds 3.0% by weight, the crystallinity of the barium titanate particles may be reduced, and there is a risk that the particles cannot be used as a raw material for electronic and optical components.
[0042] The barium titanate particles according to the present invention preferably have high purity.
[0043] This is because using barium titanate particles that are not of high purity may adversely affect electronic and optical components.
[0044] Examples of impurity elements in the barium titanate particles of the present invention include Si, S, Cl, Ca, Fe, and Sr derived from the main raw material, and N, Na, and K derived from the neutralizing agent.
[0045] The impurity elements are each preferably at 300 ppm or less, more preferably at 200 ppm or less, and further preferably at 100 ppm or less.
[0046] The amounts of N, Na, and K derived from the neutralizing agent are each preferably 30 ppm or less, more preferably 20 ppm or less, and further preferably 10 ppm or less.
[0047] The coefficient of variation of the primary particle diameter of the barium titanate particles is an index which means that the smaller the value, the better the particle size distribution of the primary particle diameter.
[0048] The coefficient of variation of the primary particle size of the barium titanate particles according to the present invention is preferably 0.30 or less, more preferably 0.29 or less, and even more preferably 0.28 or less. The lower limit of the coefficient of variation of the primary particle size of the barium titanate particles according to the present invention is about 0.10.
[0049] If the coefficient of variation of the primary particle size of the barium titanate particle powder exceeds 0.30, it is difficult to say that the particle size distribution of the primary particle size is excellent, and there is a risk that the surface of the dried film obtained by dispersing the barium titanate particle powder in a solvent will be rough, or that electronic and optical components using the barium titanate particle powder will be adversely affected.
[0050] On the other hand, if the coefficient of variation of the primary particle size of the barium titanate particles is less than 0.10, it is difficult to industrially produce a particle powder in which the existence probability of fused primary particles satisfies the range of 1% to 15%.
[0051] The Ba / Ti composition ratio of the barium titanate particles according to the present invention is preferably 0.970 to 1.030, more preferably 0.972 to 1.025, and further preferably 0.975 to 1.010.
[0052] If the Ba / Ti composition ratio of the barium titanate particles is less than 0.970, a large amount of unreacted titanium remains, resulting in barium titanate with poor crystallinity, which may result in a decrease in dielectric constant and refractive index.
[0053] If the Ba / Ti composition ratio of the barium titanate particles exceeds 1.030, there is a risk that impurities such as barium carbonate will increase and that the dielectric constant and refractive index will decrease.
[0054] The barium carbonate BaCO3 content of the barium titanate particles according to the present invention is preferably 0.3 weight (wt) % or less, more preferably 0.25 wt % or less, and further preferably 0.20 wt % or less.
[0055] If the barium carbonate content of the barium titanate particle powder exceeds 0.3% by weight, the dielectric constant and refractive index may decrease. The lower limit of the barium carbonate content is about 0.0% by weight.
[0056] The BET specific surface area of the barium titanate particles according to the present invention is 15 m 2 / g~75m 2 / g, more preferably 18m 2 / g~70m 2 / g.
[0057] BET specific surface area is 15m 2 / g~75m 2 This is because, within the range of 1 / g, the converted particle size based on the BET specific surface area and true density is close to the average primary particle size, and the barium titanate particles can be regarded as having high crystallinity.
[0058] The crystallite size of the barium titanate particles according to the present invention is preferably 18 nm to 85 nm, and more preferably 20 nm to 80 nm.
[0059] This is because when the crystallite size is 18 nm to 85 nm, each particle is close to being a single crystal.
[0060] The lattice constant ratio c / a of the barium titanate particles according to the present invention is preferably from 1.001 to 1.025, and more preferably from 1.002 to 1.020.
[0061] If the lattice constant ratio c / a is less than 1.001, the barium titanate has low crystallinity and there is a risk of the dielectric constant and refractive index decreasing, whereas it is difficult to produce barium titanate with a lattice constant ratio c / a exceeding 1.025.
[0062] In addition, when the average diameter of the primary particles becomes small, in the case of barium titanate particles, the lattice constant ratio c / a approaches 1 due to the particle size effect.
[0063] The unit cell volume V of the barium titanate particles according to the present invention cell is 65.30 Å 3 It is preferable that the thickness is equal to or less than 65.20 Å. 3 The following is the result.
[0064] Unit cell volume V cell is 65.30 Å 3 If the volume exceeds 100%, it means that some impurity element is contained in a large amount, and it is difficult to say that the barium titanate is of high purity and high crystallinity. cell The lower limit is 64.30 Å 3 That's about it.
[0065] Next, a dispersion containing the barium titanate particles according to the present invention will be described.
[0066] The dispersion medium according to the present invention may be either aqueous or non-aqueous.
[0067] Examples of the dispersion medium for the aqueous dispersion, i.e., the aqueous solvent, include water, or alcohol-based solvents such as methyl alcohol, ethyl alcohol, propyl alcohol, isopropyl alcohol, and butyl alcohol; glycol ether-based solvents such as methyl cellosolve, ethyl cellosolve, propyl cellosolve, and butyl cellosolve; oxyethylene or oxypropylene addition polymers such as diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, tripropylene glycol, and polypropylene glycol; alkylene glycols such as ethylene glycol, propylene glycol, and 1,2,6-hexanetriol; and water-soluble organic solvents such as glycerin and 2-pyrrolidone.
[0068] The aqueous solvent may be used alone or in combination of two or more kinds depending on the intended use.
[0069] Examples of dispersion media for solvent-based dispersions, i.e., non-aqueous solvents, include aromatic hydrocarbons such as toluene and xylene; ketones such as methyl ethyl ketone and cyclohexanone; terpenes such as terpineol, dihydroterpineol, and dihydroterpineyl acetate (low polarity solvent); amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether. Examples of such esters include ether alcohols such as ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and other ether acetates; acetate esters such as ethyl acetate, butyl acetate, isobutyl acetate, and other lactate esters; lactate methyl ester, lactate ethyl ester, lactate propyl ester, and other lactate esters; cyclic esters such as ethylene carbonate, propylene carbonate, γ-butyrolactone, and other various monomers.
[0070] The non-aqueous solvent may be used alone or in combination of two or more kinds depending on the intended use.
[0071] The concentration of the barium titanate particles in the dispersion according to the present invention is preferably 5% by weight to 60% by weight, more preferably 10% by weight to 55% by weight, and further preferably 15% by weight to 50% by weight.
[0072] If the concentration of the barium titanate particles in the dispersion according to the present invention is less than 5% by weight, the productivity is low, whereas if it exceeds 60% by weight, it is difficult to say that a slurry with high fluidity is produced.
[0073] The dispersion according to the present invention may contain additives such as a dispersant, a resin, an antifoaming agent, and an auxiliary, if necessary.
[0074] The dispersant in the present invention can be appropriately selected and used depending on the type of barium titanate particle powder and dispersion medium used, and examples thereof include organic silicon compounds such as alkoxysilanes, silane-based coupling agents and organopolysiloxanes, organic titanium compounds such as titanate-based coupling agents, organic aluminum compounds such as aluminate-based coupling agents, organic zirconium compounds such as zirconate-based coupling agents, surfactants, and polymer dispersants.
[0075] The dispersants may be used alone or in combination of two or more.
[0076] Examples of the organosilicon compound include alkoxysilanes such as methyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, butyltriethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, tetraethoxysilane, and tetramethoxysilane; silane-based coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, and γ-chloropropyltrimethoxysilane; and organopolysiloxanes such as polysiloxane, methylhydrogenpolysiloxane, and modified polysiloxane.
[0077] The organic titanium compounds include isopropyl triisostearoyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, isopropyl tri(N-aminoethyl aminoethyl) titanate, tris(dioctyl pyrophosphate)ethylene titanate, isopropyl dioctyl pyrophosphate titanate, isopropyl tris(dodecylbenzenesulfonyl) titanate, titanium tetra-n-butoxide, titanium tetra-2-ethylhexoxy Examples of the phosphate esters include tetraisopropyl bis(dioctyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, tetraoctyl bis(ditridecyl phosphate) titanate, tetra(2-2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphate titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, and bis(dioctyl pyrophosphate)ethylene titanate.
[0078] Examples of the organic aluminum compound include acetoalkoxyaluminum diisopropylate, aluminum diisopropoxymonoethylacetoacetate, aluminum trisethylacetoacetate, and aluminum trisacetylacetonate.
[0079] Examples of the organic zirconium compound include zirconium tetrakis acetylacetonate, zirconium dibutoxy bis acetylacetonate, zirconium tetrakis ethyl acetoacetate, zirconium tributoxy monoethyl acetoacetate, and zirconium tributoxy acetylacetonate.
[0080] Examples of the surfactant include anionic surfactants such as fatty acid salts, sulfate salts, sulfonate salts, and phosphate salts; nonionic surfactants such as polyethylene glycol-type nonionic surfactants such as polyoxyethylene alkyl ethers and polyoxyethylene aryl ethers, and polyhydric alcohol-type nonionic surfactants such as sorbitan fatty acid esters; cationic surfactants such as amine salt-type cationic surfactants and quaternary ammonium salt-type cationic surfactants; and amphoteric surfactants such as alkyl betaines and alkyl imidazolines, such as alkyl dimethyl amino acetate betaines.
[0081] Examples of the polymer dispersant include a styrene-acrylic acid copolymer, a styrene-maleic acid copolymer, a polycarboxylic acid, and a salt thereof.
[0082] The amount of dispersant added depends on the total surface area of the barium titanate particle powder in the dispersion and may be appropriately adjusted depending on the application of the barium titanate particle powder dispersion and the type of dispersant. Generally, however, by adding 0.01% by weight to 100% by weight of dispersant to the barium titanate particle powder in the dispersion medium, the barium titanate particle powder can be uniformly and finely dispersed in the dispersion medium and dispersion stability can also be improved.
[0083] The dispersant may be added directly to the dispersion medium, or may be preliminarily applied to the barium titanate particles.
[0084] The method of pre-treatment is not limited as long as a dispersant or additive is attached, coated, or reacted with the whole or part of the surface of the barium titanate fine particles. An example of the method is the attachment using a paint conditioner.
[0085] Next, a method for producing the barium titanate particles according to the present invention will be described.
[0086] The method for producing the barium titanate particles according to the present invention will be described using a solution reaction in an aqueous solvent. However, the powder may be produced by a solid phase method in which raw materials are mixed, pulverized and calcined, or by a sol-gel method in which a powder is produced by hydrolysis of a metal alkoxide.
[0087] The production method in the present invention is a solution reaction, an example of which is shown in FIG.
[0088] The first step is a step of producing barium titanate from a titanium raw material and a barium raw material, the second step is a step of preparing a reaction solution containing the produced barium titanate, and the third step is a step of producing the desired barium titanate particle powder by a grain growth reaction of barium titanate.
[0089] The method for producing barium titanate particle powder according to the present invention is a method for producing barium titanate particle powder by a solution reaction, and includes at least a first step of producing barium titanate using a titanium raw material which is a slurry containing titanic acid represented by TiO2·nH2O, where n is 0.5 to 1.5 and the crystallite size of the anatase component is 2 nm to 10 nm, a second step of adjusting the titanium concentration of the reaction solution to 0.85 mol / L to 2.50 mol / L, and a third step of growing grains of barium titanate at 60°C to 155°C.
[0090] First, the preparation of a titanium raw material in the first step of the method for producing barium titanate particles according to the present invention will be described.
[0091] The titanium raw material in the present invention is a slurry containing titanate TiO2·nH2O, which will be described later.
[0092] Generally, titanium tetrachloride (TiCl4) is used as a titanium compound that is a starting material for producing barium titanate particles.
[0093] Since Cl in titanium tetrachloride is an impurity element, it is known that titanic acid derived from titanium tetrachloride is washed with water to produce high-purity barium titanate.
[0094] Generally, when titanic acid is produced from TiCl4 in a solution reaction in an aqueous solvent, referring to Non-Patent Document 2 and the like, the following neutralization reaction represented by (formula A), the dehydration reaction represented by (formula B), and the hydrolysis reaction represented by (formula C) are representative.
[0095] (Neutralization reaction) (Formula A)TiCl4+4MOH→Ti(OH)4+4MCl
[0096] In formula A, M is Na, K, NH, etc., and MOH is a neutralizing agent. The neutralizing agent is not particularly limited, and may be a hydroxide of a divalent metal such as M'(OH)2 or a carbonate such as M'CO3, and M' is Ca, etc.
[0097] (Dehydration reaction) (Formula B)TiO2·nH2O→TiO2·(n-1)H2O+H2O
[0098] In formula B, n≦2. Here, in TiO2·nH2O, when n=2 it is orthotitanic acid, and when n=1 it is metatitanic acid. Orthotitanic acid is expressed as Ti(OH)4 or H4TiO4, and metatitanic acid is expressed as TiO(OH)2 or H2TiO3.
[0099] Orthotitanic acid is an amorphous or low-crystalline titanic acid, while metatitanic acid is treated as an aggregate of crystalline anatase microcrystals. The resulting titanic acid, TiO2·nH2O (n≦2), appears as a white precipitate or white dispersion.
[0100] (Hydrolysis reaction) (Formula C)TiCl4+(m+2)H2O→TiO2 mH2O+4HCl
[0101] In formula C, m is 0≦m≦2 and depends on the titanium tetrachloride concentration in the reaction solution, pH, impurities in the solution, etc., but when the temperature and pH are relatively high, metatitanic acid with m ≒ 1 is produced.
[0102] The hydrolysis reaction of titanium tetrachloride refers to the reaction in which a white precipitate or white dispersion is formed when water is added to titanium tetrachloride in the form of a transparent solution, or when water is added to titanium tetrachloride and a white precipitate or white dispersion is formed after a certain period of time has passed.
[0103] The titanium raw material in the present invention is a slurry containing titanic acid obtained based on the reactions of the above (Formula A), (Formula B) and (Formula C).
[0104] The titanic acid in the present invention is preferably obtained by carrying out a dehydration reaction of (formula B) after a neutralization reaction of (formula A). That is, it is preferable to obtain the titanic acid by dropping a neutralizing agent at a low temperature to industrial titanium chloride (Cl / Ti<4) diluted with water to carry out a neutralization reaction.
[0105] The temperature at which the neutralizing agent is dropped is preferably in the range of 10°C to 60°C, and more preferably 20°C to 55°C.
[0106] If the reaction temperature of (A) exceeds 60°C during the dropwise addition, the hydrolysis reaction of (C) may proceed due to heat generation during neutralization of titanium chloride, whereas if the reaction temperature is less than 10°C, it is difficult to control industrially.
[0107] In the present invention, the MOH / Cl value [molar ratio], which is the ratio of neutralizing agent MOH to Cl in titanium chloride, is preferably 0.60 to 1.50, more preferably 0.70 to 1.40, and further preferably 0.80 to 1.30.
[0108] If the MOH / Cl value exceeds 1.50, M-containing titanate is produced, and it is difficult to remove M by washing with water, and there is a risk that a large amount of the impurity M will remain in the obtained barium titanate particle powder. On the other hand, if the MOH / Cl value is less than 0.60, unreacted titanium chloride will remain and be washed away during washing with water, which may result in a decrease in the yield of the obtained barium titanate particle powder.
[0109] In the method for producing barium titanate particles according to the present invention, the Ti concentration after the neutralization reaction of (formula A) and during the dehydration reaction of (formula B) is preferably 0.2 mol / L to 3.5 mol / L, more preferably 0.3 mol / L to 3.2 mol / L, and even more preferably 0.35 mol / L to 3.0 mol / L.
[0110] After the neutralization reaction (formula A), the dehydration reaction (formula B) is preferably carried out at 50°C to 85°C, more preferably 52°C to 83°C.
[0111] If the temperature of the dehydration reaction (formula B) is less than 50° C., the dehydration reaction is unlikely to occur, whereas if the temperature exceeds 85° C., there is a risk that titanic acid, which has low reactivity with barium, will be produced.
[0112] The time for the dehydration reaction (formula B) is preferably 30 minutes to 24 hours. If it is less than 30 minutes, the dehydration reaction is unlikely to occur, and if it exceeds 24 hours, it is not industrially viable.
[0113] The dehydration reaction results in titanic acid (TiO2·nH2O).
[0114] The neutralization reaction through the dehydration reaction are preferably carried out in a state where the reaction solution is exposed to a gas in an oxidizing atmosphere.
[0115] In the case of an inert gas atmosphere, impurities are likely to remain in the titanate obtained after the subsequent water washing step, making it difficult to obtain high-purity barium titanate particles.
[0116] The oxidizing atmosphere may be a pure oxygen atmosphere or an air atmosphere, or the reaction solution may be actively exposed to the oxidizing atmosphere by bubbling air into the reaction solution.
[0117] The titanium raw material for the first step in the present invention is preferably a mixed titanic acid, more preferably a mixed titanic acid of orthotitanic acid obtained by a neutralization reaction (formula A) and metatitanic acid obtained by a dehydration reaction (formula B), and even more preferably does not contain any hydrolysate formed by the reaction of titanium chloride in a strongly acidic atmosphere (formula C).
[0118] In addition, the titanium raw material for the first step in the present invention can also be produced by preparing metatitanic acid at a pH of 0.5 to 3.5 and a temperature of 40°C to 80°C according to (formula C), and mixing it with titanic acid obtained by mixing orthotitanic acid obtained by neutralization reaction (formula A) and metatitanic acid obtained by dehydration reaction (formula B).
[0119] In order to wash away impurity elements contained in the titanic acid that is the titanium raw material in the first step, washing with water may be carried out.
[0120] The end point of the water washing is when the filtrate conductivity reaches 200 μS / cm, and the impurity elements contained in the titanic acid after washing can be measured.
[0121] The amount of each of the impurity elements contained in the titanic acid after washing with water is preferably 1000 ppm or less, more preferably 800 ppm or less, and further preferably 500 ppm or less.
[0122] If the impurity elements exceed 1000 ppm each, there is a risk that any of the impurity elements Si, S, Cl, Ca, Fe, and Sr derived from the main raw material will exceed 200 ppm in the barium titanate particle powder obtained from the third step onwards, and there is a risk that any of the alkali metal elements N, Na, and K derived from the neutralizing agent will exceed 20 ppm.
[0123] When the titanic acid serving as the titanium raw material in the first step is expressed as TiO2·nH2O, n is in the range of 0.5≦n≦1.5, and more preferably 0.55≦n≦1.4.
[0124] If n exceeds 1.5, washing with water becomes difficult, and impurity elements tend to remain in the titanic acid. In addition, the crystallinity of the obtained barium titanate is low, the particle surface is not smooth, and there is a risk of an increased probability of fused primary particles being present.
[0125] If n is less than 0.5, the reactivity with Ba in the second step may be low, resulting in barium titanate with low crystallinity.
[0126] The crystallite size of the anatase component of the obtained titanic acid is 2 nm to 10 nm, and more preferably 3 nm to 9 nm.
[0127] If the crystallite size exceeds 10 nm, the reactivity with the barium raw material in the solution reaction described below decreases, making it difficult to produce fine barium titanate, and if the crystallite size is less than 2 nm, it becomes difficult to wash the titanic acid with water. In addition, it becomes difficult to increase the concentration in the solution reaction, and there is a risk of a decrease in the production rate of barium titanate.
[0128] In the first step, a titanium source and a barium source are reacted in an aqueous solution to produce barium titanate particles.
[0129] An example of the barium source in the present invention is an aqueous barium hydroxide solution.
[0130] The barium raw material is preferably of high purity. The starting barium raw material is not particularly limited, but barium hydroxide is exemplified.
[0131] A reaction solution is prepared as a mixture of the obtained titanium raw material and barium raw material. The titanium raw material and the barium raw material are preferably reacted in an alkaline environment, and the initial OH concentration is preferably 0.8 mol / L to 2.0 mol / L, and more preferably 0.85 mol / L to 1.8 mol / L.
[0132] The raw material mixing temperature for preparing the reaction solution in the first step is preferably in the range of 60°C to 105°C, more preferably 65°C to 100°C, and further preferably 70°C to 95°C.
[0133] To produce barium titanate in the first step, the raw material mixing temperature is preferably maintained for 2 to 10 hours, more preferably for 3 to 8 hours. Through the first step, a solution reaction slurry is obtained.
[0134] The molar ratio of Ba / Ti in the reaction solution in the first step is preferably 0.80 to 1.25, more preferably 0.85 to 1.20, and even more preferably 0.9 to 1.15. The stoichiometric composition of barium titanate is Ba / Ti=1, and if the Ba / Ti in the reaction solution exceeds 1, the excess Ba can be reduced by washing with water.
[0135] The titanium concentration in the reaction solution in the first step is preferably 0.30 mol / L to 0.80 mol / L, and more preferably 0.35 mol / L to 0.75 mol / L.
[0136] The gas that comes into contact with the solution during the reaction is preferably an oxidizing gas that does not contain carbon dioxide or an inert gas such as high-purity nitrogen, in order to prevent the formation of barium carbonate.
[0137] The solids produced in the solution reaction slurry obtained in the first step can be obtained by filtering, washing with water, drying the cake at 120° C. or less, and pulverizing. The filtering and washing should be performed until the filtrate has an electrical conductivity of 0.2 mS / cm.
[0138] The crystallite size of the barium titanate in the resulting solid content is preferably 15 nm to 70 nm, and more preferably 18 nm to 60 nm.
[0139] Next, the second step in the present invention will be described.
[0140] The titanium concentration in the reaction solution in the second step of the present invention is 0.85 mol / L to 2.50 mol / L, and more preferably 0.90 mol / L to 2.20 mol / L.
[0141] The titanium concentration of the reaction solution can be adjusted, for example, by concentrating the reaction slurry obtained in the first step by settling, by concentrating after washing with water, or by adding a barium source and a titanium source.
[0142] The Ba / Ti ratio in the second step of the present invention is preferably from 1.02 to 1.50 molar ratio, more preferably from 1.05 to 1.40 molar ratio.
[0143] Next, the third step in the present invention will be described.
[0144] The third step in the present invention is a step of growing grains of barium titanate.
[0145] The solution reaction temperature in the third step is preferably 60°C to 155°C, more preferably 70°C to 140°C.
[0146] When the crystallite size of the barium titanate obtained in the third step is larger than that of the barium titanate in the resulting solid content, it can be considered that grain growth of the barium titanate has occurred in the third step.
[0147] The solution reaction time in the third step in the present invention is preferably 1 hour to 15 hours, more preferably 2 hours to 13 hours.
[0148] The slurry containing the barium titanate particles obtained in the third step may be washed with water to remove impurities such as excess Ba derived from the barium raw material.
[0149] Barium titanate particles produced in an aqueous solution can be used to obtain barium titanate particle powder by removing the water used in the solution reaction. In this case, it is preferable to prevent strong aggregation of barium titanate particles by cross-linking water. For this purpose, a slurry containing barium titanate particles can be instantly dried according to a conventional method, or the barium titanate particles can be replaced with a solvent having a lower cross-linking power than water and then dried. In addition, the barium titanate particle powder dried from the slurry can be dry-pulverized to prevent strong aggregation of the particles.
[0150] The obtained barium titanate particles may be further calcined and pulverized to enhance the crystallinity. EXAMPLES
[0151] Specific examples and comparative examples of the present invention are shown below, but the present invention is not limited to these.
[0152] The powder evaluation of the barium titanate particles of the present invention was carried out as follows.
[0153] The surface, shape, primary particle size, and fusion of primary particles of the barium titanate particle powder were observed and quantified by analyzing bright-field images obtained using a transmission electron microscope TEM "JEM-1010" [manufactured by JEOL Ltd.].
[0154] To facilitate TEM observation, 2-acetoxy-1-methoxypropane was used as the solvent and polymeric dispersant ED-153 (Kusumoto Chemicals Co., Ltd.) was used as the dispersant, and the mixture was dispersed ultrasonically for 5 minutes. The obtained slurry was placed on a TEM mesh, dried, and observed by TEM.
[0155] 500 primary particles in the obtained image were measured using image analysis type particle size distribution measurement software "Mac-View" [manufactured by Mountec Co., Ltd.], and the average primary particle size was calculated from the number average of the primary particle sizes. In addition, the obtained standard deviation was divided by the average diameter of the primary particles to obtain the coefficient of variation of the primary particle size.
[0156] Using the black and white inversion function of the general-purpose software ImageJ, the particles were classified into primary particles without interparticle fusion and particles with fusion between primary particles. Primary particles without interparticle fusion were counted as one primary particle. On the other hand, fused particles in which no boundary was observed between primary particles and a gourd shape was observed, one fused particle was counted as two fused primary particles to obtain the number of fused primary particles. The number of fused primary particles was divided by the total number of primary particles and expressed as a percentage to calculate the probability of the presence of fused primary particles.
[0157] The Ba / Ti composition ratio was measured using a fluorescent X-ray analyzer "Simultix12" [manufactured by Rigaku Corporation] and expressed as a molar ratio. Also, a part of the solution reaction slurry obtained in the first step was washed with water, and the solid content obtained when the filtrate had an electric conductivity of 0.2 mS / cm or less was regarded as the product solid content.
[0158] The BET specific surface area was measured using a fully automatic specific surface area measuring device "Macsorb HM model-1208" [manufactured by Mountec Co., Ltd.] after drying and degassing for 10 minutes at 250°C under nitrogen gas.
[0159] The particle size of the aggregated particles in the aqueous solvent was measured using a laser diffraction / scattering particle size distribution analyzer, Microtrac MT3300EXII (manufactured by Microtrac Bell Co., Ltd.).
[0160] The particles were dispersed ultrasonically for 5 minutes in 20 mL of a 0.2 wt % aqueous solution of sodium hexametaphosphate dispersant, and then the particle size distribution of the aggregated particle size in the aqueous solvent was measured.
[0161] From the cumulative frequency distribution of particle size distribution obtained by measuring the particle size distribution of aggregate particle size in an aqueous solvent, the D 50 and 95% diameter D 95 Represented by D 95 / D 50 The value was calculated.
[0162] Identification of the crystalline phase, calculation of the crystallite size and crystal structure parameters of barium titanate, and anatase crystallite size of TiO2·nH2O were measured using a powder X-ray diffraction apparatus “SmartLab” [Rigaku Corporation].
[0163] X-ray diffraction patterns were measured through a monochromator under the conditions of Cu-Kα, 40 kV, and 200 mA, with a step rate of 0.02° at 15≦2θ(deg.)≦90 and a rate of 3 deg. / min.
[0164] The crystal structure parameters such as lattice constants were analyzed by the Rietveld method. The tetragonality, which indicates the crystallinity of barium titanate particles, was expressed as the lattice constant ratio c / a. cellwas calculated.
[0165] The barium carbonate was quantified using the same powder X-ray diffractometer, with measurements at 15≦2θ(deg.)≦45, in steps of 0.02°, at 1 deg. / min., and calculated using the Rietveld method.
[0166] The amount of impurities was quantified by the internal standard method using an inductively coupled plasma optical emission spectrometer (ICP-OES) "Optima8300" (PerkinElmer Japan Co., Ltd.).
[0167] Samples with impurity elements Si, S, Cl, Ca, Fe, and Sr of 200 ppm or less, or impurity alkali metal elements N, Na, and K of 20 ppm or less by ICP-OES were rated as "good."
[0168] Ignition loss was calculated by weighing a 10 g sample before and after heating at 1200°C for 2 hours, dividing the weight by the weight before heat treatment, and expressed as a percentage by weight.
[0169] Samples whose ignition loss was less than or equal to the value calculated by the formula (4.3 - 0.04 x average primary particle size [nm]) by weight percent (wt%) were evaluated as "Good", and others were evaluated as "Poor". The results are shown in Table 3.
[0170] The n of the slurry containing the titanium raw material titanic acid, expressed as TiO2·nH2O, was evaluated by the following method.
[0171] The moisture content of the cake obtained by dehydrating the titanic acid-containing slurry was calculated from the weight loss when 1 g of the cake was dried at 25°C for 24 hours. In other words, the dry powder obtained by the drying was regarded as titanic acid TiO2·nH2O. In addition, the ignition loss of 1 g of the titanic acid-containing cake was measured after heat treatment at 700° C. for 2 hours. TiO2 powder was obtained by heat treatment at 700° C. for 2 hours, and the number of moles of titanium in 1 g of the cake was calculated. In addition, the difference between the sample weight obtained by drying at 25°C and the weight obtained by heat treatment at 700°C was regarded as the difference in weight between TiO2 titanate·nH2O and TiO2 oxide, i.e., the weight of nH2O in TiO2 titanate·nH2O, and the number of moles was calculated. n was calculated from the two mole numbers obtained.
[0172] The settling velocity of the solids produced in the first step was calculated from the interface between the white slurry in which the particles are dispersed and the colorless, transparent liquid in which the particles are not dispersed. In other words, the time required for the solids to settle and concentrate to a titanium concentration of 0.9 mol / L or more was measured after removing the supernatant of the colorless, transparent liquid at the top. Samples that were able to settle and concentrate within 10 hours were evaluated as having favorable conditions and given a rating of "good", while samples whose settlement and concentration time exceeded 10 hours were given a rating of "poor". The results are shown in Table 1 as the settling rate.
[0173] [Example 1] In the first step, an industrial titanium chloride solution (Ti concentration 16.5 wt %, Cl concentration 31 wt %) was used as the main raw material titanium compound. The main raw barium compound used was industrial high-purity barium hydroxide octahydrate Ba(OH)2·8H2O. Industrial NaOH was used as the neutralizing agent. A titanium vessel of about 15 L was used for the solution reaction.
[0174] Barium hydroxide octahydrate was dissolved in warm water and the barium carbonate was removed using a filter to prepare a barium hydroxide solution, which was used as the barium source. Titanium chloride solution was weighed out so that Ti was 5 mol. NaOH was weighed out so that NaOH / Cl=1.02.
[0175] In an air atmosphere, 4 L of titanium chloride solution diluted with water was neutralized by adding 4 L of NaOH solution dropwise over a period of 1 hour so that the temperature did not exceed 60°C. Without going through hydrolysis of titanium chloride of (formula C) as much as possible, 8 L of orthotitanic acid slurry was obtained according to (formula A). The Ti concentration was 0.625 mol / L.
[0176] The obtained orthotitanic acid slurry was subjected to a partial dehydration reaction of the orthotitanic acid in the air at 70° C. for 1 hour.
[0177] It was then cooled to obtain titanic acid (TiO2·nH2O) slurry.
[0178] The obtained titanic acid slurry was filtered and washed to remove impurity elements such as Na and Cl from the titanic acid TiO2·nH2O. 5 g of the titanic acid TiO2·nH2O cake was then dried at 25°C and the impurity elements and the n value of titanic acid TiO2·nH2O were quantified. In addition, the X-ray diffraction pattern of the undried sample confirmed metatitanic acid with an anatase crystal phase and orthotitanic acid with low crystallinity as a broad peak.
[0179] The obtained titanate TiO2·nH2O had n of 1.3, anatase crystallite size of 4 nm, and the maximum impurity element was Na, 0.03 wt%. The remaining TiO2·nH2O titanate cake was peptized to prepare 5 L of TiO2·nH2O titanate-containing slurry, which was used as the titanium source.
[0180] In a high-purity nitrogen atmosphere, a slurry containing titanate TiO2·nH2O (n = 1.3) kept at 80 °C was mixed with 5 L of 80 °C barium hydroxide solution in a Ba / Ti = 1.2 molar ratio. The raw material mixture temperature was set to 80° C., and the solution reaction was carried out by maintaining the same temperature for 3 hours.
[0181] The Ti concentration of the reaction solution was 0.59 mol / L, the initial OH concentration was 1.42 mol / L, and the reaction solution volume was 10 L.
[0182] A portion of the slurry obtained in the first step was filtered, washed with water, and the cake was dried and crushed, and the resulting solid content was evaluated.
[0183] The X-ray diffraction pattern revealed that barium titanate particles were formed. The crystallite size of the barium titanate contained in the solid product is 26 nm, and the BET specific surface area is 49 m 2 / g.
[0184] The barium titanate-containing slurry (about 10 L) obtained in the first step was concentrated by precipitation to a titanium concentration of 0.9 mol / L or more within 10 hours.
[0185] In the second step, the Ti concentration of the reaction solution obtained in the first step was adjusted to 1.0 mol / L, and the Ba / Ti ratio was adjusted to 1.15.
[0186] In the third step, the resulting 5 L slurry was subjected to hydrothermal treatment at a particle growth reaction temperature of 105° C. for 3 hours to grow barium titanate particles.
[0187] After filtration, washing with water, drying and pulverization, the barium titanate particles of the present invention were obtained.
[0188] The barium titanate particles in Example 1 had an average primary particle size of 31 nm and a variation coefficient of 0.24.
[0189] The 10% diameter D of the cumulative frequency distribution of agglomerated particles in the obtained particle powder in an aqueous solvent is 10 is 0.081μm, and the 50% diameter of the cumulative frequency distribution D 50 is 0.131μm, and the 95% diameter of the cumulative frequency distribution D 95 was 0.244 μm. D 95 / D 50 The value was 1.9, which indicated that the material was easily dispersible in aqueous solvents.
[0190] The probability of fused primary particles was 13%, close to monodispersity. In addition, the ignition loss was 2.4% by weight, confirming high crystallinity.
[0191] The Ba / Ti composition ratio was 0.972 molar ratio, and the BaCO3 content was 0.1 wt%.
[0192] The crystallite size of the obtained barium titanate was 36 nm. The lattice constant ratio c / a is 1.003, the degree of tetragonality is high, and the unit cell volume V cell is 64.93 Å 3 and the content of water of crystallization was low. BET specific surface area is 36m 2 / g.
[0193] The barium titanate according to the present invention was found to have high purity because the impurity elements Si, S, Cl, Ca, Fe, and Sr derived from the main raw materials by ICP-OES were 200 ppm or less, and the impurity alkali metal elements N, Na, and K derived from the neutralizing agent were 20 ppm or less. In addition, the particle surface of the barium titanate according to the present invention was smooth.
[0194] [Examples 2 and 3] Example 2 was carried out under the same conditions as Example 1, except that the particle growth reaction temperature in the third step was changed to 130°C. Example 3 was carried out under the same conditions as Example 1, except that the particle growth reaction temperature in the third step was changed to 140°C.
[0195] FIG. 2 shows a TEM image of the barium titanate particles obtained in Example 2. The obtained image was black and white inverted and image processing was performed such that a circle was placed in the center of primary particles that were not fused to each other and fused primary particles were connected with rods.
[0196] [Example 4] The same conditions as in Example 2 were used, except that the Ba / Ti ratio in the solution reaction conditions in the first step was changed to 0.99 molar ratio, and the Ba / Ti ratio adjusted in the second step was changed to 1.40 molar ratio.
[0197] Each D of the barium titanate particle powder according to the present invention 95 / D 50 The value of was small, the probability of the presence of fused primary particles was small, and the ignition loss was also low, confirming that the material was highly crystalline and easily dispersible in aqueous solvents (Table 3).
[0198] [Comparative Example 1] Comparative Example 1 was carried out under the production conditions shown in Tables 1 and 2. The first step was carried out under the same conditions as in Example 1, except that the solution reaction conditions in the first step were a Ti concentration of 0.67 mol / L, a Ba / Ti ratio of 0.75 mol, and an initial OH concentration of 1.01 mol / L.
[0199] The second and third steps were carried out under the same conditions as in Example 1, except that the solution reaction condition in the second step was set to a Ba / Ti molar ratio of 1.40.
[0200] FIG. 3 shows a TEM image obtained in Comparative Example 1. Figure 3 was image processed in the same manner as Figure 2. As shown in Figure 3, the particle powder obtained in Comparative Example 1 had a large amount of fused primary particles. As shown in Table 3, the powder characteristics showed an average primary particle diameter of 31 nm. However, the probability of fused primary particles was high, and the coefficient of variation of the primary particles was also high.
[0201] [Comparative Example 2] The first step was carried out under the same conditions as in Example 1, except that the solution reaction conditions in the first step were a Ti concentration of 0.50 mol / L, a Ba / Ti ratio of 1.80 mol, and an initial OH concentration of 1.80 mol / L. The second and third steps were carried out under the same conditions as in Example 2, except that the solution reaction conditions in the second step were set to a Ba / Ti molar ratio of 1.55. The average primary particle size was 26 nm, but the probability of the presence of fused primary particles was high (Table 3).
[0202] [Comparative Example 3] The conditions not described below were the same as in Example 1.
[0203] Barium hydroxide octahydrate was dissolved in warm water, and the barium carbonate was removed using a filter to prepare a barium hydroxide solution, which was used as a neutralizing agent. The barium hydroxide solution was weighed so that OH / Cl was 1.02. In an air atmosphere, 2.5 L of 80°C barium hydroxide solution was added dropwise to 2.5 L of 40°C titanium chloride solution diluted with water over one hour to neutralize the solution. 5 L of orthotitanic acid slurry was obtained according to (Equation A) without hydrolysis of titanium chloride (Equation C) as much as possible. The Ti concentration was 1.0 mol / L. The temperature was raised to 80°C to prepare the titanium raw material.
[0204] The titanium raw material was mixed with 5 L of barium hydroxide solution maintained at 80° C. A barium titanate-containing slurry was obtained by a solution reaction at 80° C. for 3 hours. Without going through the second and third steps, the slurry was appropriately washed with water to obtain barium titanate with a Ba / Ti=0.998 molar ratio (Table 3).
[0205] The probability of the existence of the obtained fused primary particles is high, the ignition loss is high, and D 95 / D 50 The value of was also high. The impurity Cl was more than 200 ppm, which meant that this was not high-purity barium titanate (Table 3).
[0206] [Comparative Example 4] The conditions not described below were the same as in Example 1.
[0207] 2.5 L of titanium chloride solution diluted with water was neutralized by adding 2.5 L of NaOH solution dropwise over one hour to obtain 5 L of orthotitanic acid slurry. The Ti concentration was 1.0 mol / L. The orthotitanic acid slurry was heated to 80° C. and used as a titanium raw material.
[0208] The obtained titanium raw material was mixed with 5 L of a barium hydroxide solution kept at 80°C. A barium titanate-containing slurry was obtained by a solution reaction at 80° C. for 3 hours. After adequate washing with water, a cake containing the product solid content shown in Table 1 was obtained. A part of the cake was dried to obtain the powder characteristics of the product solid content shown in Table 1. The remaining cake was peptized with pure water, and the solution reaction of the second and third steps was carried out under the production conditions shown in Table 2.
[0209] [Comparative Example 5] The production conditions shown in Tables 1 and 2 were the same as those in Comparative Example 4, except that the Ba / Ti molar ratio in the solution reaction conditions in the first step was changed to 0.90.
[0210] As shown in Table 3, the obtained samples had a high probability of existence of fused primary particles. Furthermore, the impurity (Na) content in Comparative Example 4 and Comparative Example 5 was 20 ppm or more, and thus the samples were not high-purity barium titanate.
[0211] [Comparative Examples 6 to 12] Comparative Examples 6 to 12 were carried out under the manufacturing conditions shown in Table 1, based on the conditions of Comparative Example 4. As shown in Table 1, barium titanate was not produced, or a particle powder with the desired crystallite size was not obtained. Therefore, the second and subsequent steps were not carried out.
[0212] [Comparative Example 13] Barium titanate particles were produced with reference to Example 1 of JP 2005-289668 A (Patent Document 1), except that the main raw materials, neutralizing agent, and other experimental equipment were the same as those in Example 1 of the present invention.
[0213] The hydrous titanium oxide used had a single anatase phase and a crystallite size of 12 nm. The n of titanate TiO2·nH2O was 0.4. The sample obtained after the hydrothermal treatment was a barium titanate particle powder, with a high probability of fused primary particles (19%) and a high ignition loss (3.1% by weight).
[0214] [Comparative Example 14] Barium titanate particles were produced with reference to Example 6 of JP 2005-289668 A (Patent Document 1). However, the hydrothermal treatment temperature was changed to 150° C., and particles of 50 nm size were designed. In addition, the main raw materials, neutralizing agent, and other experimental equipment were in accordance with Example 1 of the present invention.
[0215] The titanate TiO2·nH2O obtained by neutralizing titanium chloride had an n of 1.8. No anatase phase was detected in the X-ray diffraction pattern obtained. The sample obtained after hydrothermal treatment was barium titanate particle powder, and the probability of the existence of fused primary particles was high at 17%. The impurity Cl was more than 200 ppm, so it was not high-purity barium titanate.
[0216] Table 1 shows the production conditions for the first step in the examples and comparative examples, and Table 2 shows the production conditions for the second and third steps. The powder properties of the examples and comparative examples are shown in Table 3.
[0217] [Table 1]
[0218] [Table 2]
[0219] [Table 3]
[0220] FIG. 5 is a plot of the ignition loss shown in Table 3 against the average primary particle size. The dotted line indicates the boundary line of present invention 4 (formula: 4.3-0.04 × average primary particle diameter), and if the value is below this boundary line, it indicates that the ignition loss (wt %) obtained by the above formula is satisfied, and it means that the particle powder is highly crystalline.
[0221] [Dispersibility in organic solvents] The barium titanate particles obtained in Example 1 and Comparative Example 3 were evaluated as dispersions.
[0222] The dispersibility of the sample is calculated by the dispersion time in the media and the D of the 50% diameter of the cumulative frequency distribution of the aggregate particle diameter in an organic solvent by dynamic light scattering method. 50 It was evaluated as follows.
[0223] D 50 was measured using "FPAR-1000" [manufactured by Otsuka Electronics Co., Ltd.]. Zirconia beads are used as the media. 50 The value of D reaches a value where it no longer changes over time. 50 Reached D 50 is lower and can be reached in a shorter time. 50 When the above result was obtained, the sample was regarded as being easily dispersible.
[0224] The samples of Example 1 and Comparative Example 3 were each weighed out at 80 g. Next, 400 g of zirconia beads having a diameter of 2 mm, 120 g of dihydroterpinyl acetate as an organic solvent, and 9.6 g of ED series (manufactured by Kusumoto Chemicals Co., Ltd.) as a dispersant were added to a high-density polyethylene container. After 24 hours of ball milling, the beads and the slurry were separated. The resulting slurry was mixed with 400 g of zirconia beads with a diameter of 50 μm and dispersed in a paint conditioner. 10 cc of the slurry was withdrawn every hour and the particle size distribution was measured by dynamic light scattering.
[0225] The sample of Example 1 had a median diameter D 50 = 97 nm, after 2 hours D 50 = 76 nm, and then the median diameter D 50 was constant.
[0226] On the other hand, the sample of Comparative Example 3 had a median diameter D 50 = 98 nm, D after 4 hours 50 = 74 nm, and then the median diameter D 50 was constant. reach D 50 The D 50 It took about 4 hours to obtain D 50 Therefore, Example 1 according to the present invention was considered to be an easily dispersible barium titanate particle powder. In addition, the achievement D 50 When this was obtained, chipping due to media dispersion was observed in the sample of Comparative Example 3.
[0227] From these results, it is estimated that the barium titanate particle powder of the present invention is fine and has very little fusion between primary particles, has a small agglomerated particle size, and is highly crystallinity, so that the Ba / Ti composition ratio is as close to the stoichiometric composition as possible, has good dispersibility, and suffers from little chipping due to dispersion.
[0228] Therefore, when the barium titanate particle powder according to the present invention is used as a co-material for the Ni internal electrode layer of an MLCC, it is highly likely that an excellent MLCC can be obtained, and the barium titanate particle powder is suitable as a raw material for small, high-performance electronic and optical components. [Industrial Applicability]
[0229] The barium titanate particles according to the present invention are fine with an average primary particle diameter of 20 nm to 80 nm, but have little fusion between primary particles and a narrow particle size distribution of agglomerated particle diameters, and therefore can be easily dispersed in various solvents. In addition, because it has low ignition loss and high crystallinity, this barium titanate particle powder can be suitably used as a grain growth inhibitor during sintering of Ni internal electrode layers in MLCCs, or as a raw material for high-capacity capacitors or high-transmittance optical films. Therefore, the present invention has high industrial applicability.
Claims
1. The average primary particle diameter is 20 nm or more and 80 nm or less, and the 50% diameter D of the cumulative frequency distribution of aggregated particles in an aqueous solvent is 50 and 95% diameter D 95 D represented by 95 / D 50 The barium titanate particle powder has a value of 1.2 or more and 5.0 or less, a probability of existence of fused primary particles is 1% or more and 15% or less, and an ignition loss is 3.0% by weight or less.
2. 2. The barium titanate particles according to claim 1, wherein the coefficient of variation of the primary particle size is 0.30 or less.
3. 3. The barium titanate particles according to claim 1, wherein the Ba / Ti composition ratio is 0.970 or more and 1.030 or less, and the barium carbonate content is 0.3 wt % or less.
4. 2. The barium titanate particles according to claim 1, wherein the ignition loss is 4.3-0.04 x average primary particle diameter)% by weight or less.
5. A dispersion comprising the barium titanate particles according to claim 1.
6. A method for producing barium titanate particles by solution reaction, comprising the steps of: 2 ・nH 2 The present invention relates to a method for producing barium titanate particle powder, the method comprising: a first step of producing barium titanate using a titanium raw material having a slurry containing titanic acid represented by the formula (I)-O, n being 0.5 or more and 1.5 or less, and having an anatase component with a crystallite size of 2 nm or more and 10 nm or less; a second step of adjusting the titanium concentration of the reaction solution to 0.85 mol / L or more and 2.50 mol / L or less; and a third step of growing grains of the barium titanate at 60°C or more and 155°C or less.
7. The method for producing barium titanate particles according to claim 6, wherein the solution reaction conditions in the first step are: raw material mixing temperature is 65°C or higher and 105°C or lower; Ba / Ti is 0.80 molar ratio or higher and 1.25 molar ratio or lower; and initial OH concentration is 0.8 mol / L or higher and 2.0 mol / L or lower.
8. 8. The method for producing barium titanate particles according to claim 6, wherein the barium titanate crystallite size in the solid content produced in the first step is 15 nm or more and 70 nm or less.
9. The method for producing barium titanate particles according to claim 6, wherein in the second step, the Ba / Ti ratio in the reaction solution is set to 1.02 molar ratio or more and 1.50 molar ratio or less.
Citation Information
Patent Citations
Tetragonal barium titanate particulate powder and method for manufacturing the same
JP2005289668A